2012
DOI: 10.1089/cyber.2011.0324
|View full text |Cite
|
Sign up to set email alerts
|

“They Are Happier and Having Better Lives than I Am”: The Impact of Using Facebook on Perceptions of Others' Lives

Abstract: Facebook, as one of the most popular social networking sites among college students, provides a platform for people to manage others' impressions of them. People tend to present themselves in a favorable way on their Facebook profile. This research examines the impact of using Facebook on people's perceptions of others' lives. It is argued that those with deeper involvement with Facebook will have different perceptions of others than those less involved due to two reasons. First, Facebook users tend to base ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
545
3
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 871 publications
(662 citation statements)
references
References 30 publications
37
545
3
18
Order By: Relevance
“…One possible reason for these findings is that Facebook provides women with a means for comparing themselves on a broad range of dimensions (beyond just appearance), such as social status and life experiences. For THE EFFECT OF FACEBOOK ON BODY IMAGE AND MOOD 22 example, similar to the findings of Chou and Edge (2012), women may be judging others on Facebook to be happier or have better lives than them, which in turn could induce a more negative mood.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…One possible reason for these findings is that Facebook provides women with a means for comparing themselves on a broad range of dimensions (beyond just appearance), such as social status and life experiences. For THE EFFECT OF FACEBOOK ON BODY IMAGE AND MOOD 22 example, similar to the findings of Chou and Edge (2012), women may be judging others on Facebook to be happier or have better lives than them, which in turn could induce a more negative mood.…”
Section: Discussionmentioning
confidence: 62%
“…Further contributing to this concern is the fact that women have reported viewing other people's Facebook profiles in order to make comparisons to those individuals (Haferkamp, Eimler, Papadakis, & Kruck, 2012). Indeed, one study found that participants who spend more time on Facebook believe that others are happier and have better lives than themselves, especially when the participants had a greater number of Facebook "friends" that they do not know personally (Chou & Edge, 2012).…”
Section: Facebook Usagementioning
confidence: 99%
“…One study found that undergraduate students who frequently used Facebook were more likely to agree with the statement, "life is unfair" (Chou & Edge, 2012). Among Serbian high school students, the amount of time on Facebook was positively correlated with higher scores on the Beck Depression Inventory (Pantic, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Labrague (2014) identified that time spent online correlated significantly with anxiety; markedly the amount of time spent on Facebook predicted higher levels of anxiety captured by the Depression, Anxiety and Stress Scale. Furthermore, research has established links between Facebook use and diminished well-being, self-esteem, and increased feelings of depression, stress, cognitive overload, and body dissatisfaction in healthy users (Chen & Lee, 2013;Chou & Edge, 2012;de Vries, de Graaf, & Nikken, 2016;Kross et al, 2013). Research suggests that frequent updates from Facebook friends and the possibility of encountering negative comments may contribute to the development of negative emotions (Labrague, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a design is used that seeks to promote a positive environment: the rapprochement of users based on criteria of affinity theoretically minimizes conflicts; in the case of Facebook, there is no disapproval button, as opposed to the "like" option, and the rejection of requests for friendships or the unmaking of friendships is not reported to the affected users and is therefore not easily perceived. However, empirical data show a recurring impression in Facebook that others are more successful and happier than we are (Chou;Edge, 2012), generating what the American Academy of Pediatrics (AAP) calls "Facebook depression." The continuity between the injunctions of accomplishment and enjoyment leads Dardot and Laval (2014) to coin the expression "performance/pleasure apparatus.…”
Section: Subjective Dimension Of Governmentalitymentioning
confidence: 99%